Animating Aesthetics: Pixar and Digital Culture - (:unkn) unknown (My University, 2015)
In the pre-digital age of cinema, animated and live-action film shared a technological basis in photography and they continue to share a basis in digital technology. This fact limits the capacity for technological inquiries to explain the persistent distinction between animated and live-action film, especially when many scholars in film and media studies agree that all moving image media are instances of animation. Understanding the distinction in aesthetic terms, however, illuminates how animation reflexively addresses aesthetic experience and its function within contexts of technological, environmental, and socio-cultural change. “Animating Aesthetics: Pixar and Digital Culture” argues that the aesthetics that perpetuate the idea of animation as a distinct mode in a digital media environment are particularly evident in the films produced by Pixar Animation Studios. As the first studio to produce a fully computer-generated animated film, Pixar has had a large and lasting influence on the standardization of computer animation. Rather than relegate animation to the domain of children’s entertainment or obfuscate its distinction from live action film, this critical study of Pixar demonstrates how its films build on an aesthetic tradition that interrogates nature, challenges epistemological stability, and explores the effects of technological change. This study includes investigations into the uncanny integrity of digital commodities in the Toy Story films, the technological sublime in Monsters, Inc., the exceptionality of the fantastic in The Incredibles, and sensorial disruption in Ratatouille. Each chapter explores aesthetic experience and how it operates as a contested domain in which norms and values are challenged, reconfigured, but also reproduced. Overall, this dissertation demonstrates how popular animated media can engage contemporary philosophical questions about how we know the world, how we understand technology and our environment, and, finally, how aesthetics are fundamental to humanistic inquiry and critical thought.
Keywords: Aesthetics; Animation; Cultural Studies; Film Studies; Media Studies; Pixar